2012
DOI: 10.1108/02651331211229741
|View full text |Cite
|
Sign up to set email alerts
|

The international commitment of late‐internationalizing Brazilian entrepreneurial firms

Abstract: where he got his PhD in Production Engineering. He did postdoctoral work at Ohio University. Before developing an academic career, he worked for several years as a top executive responsible for international decisions in Brazilian firms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
(62 reference statements)
1
28
0
2
Order By: Relevance
“…Similar with the broader entry mode research agenda, a key question in the analysed literature (14%, 10 studies) is whether EMMs follow the path dependent logic proposed by conventional applications of the Uppsala theory. Some concluded that, since pioneering is probably not an option for most of these firms, EMMs follow a gradual expansion process as they learn about foreign markets and benefit from being fast market followers versus late entrants (Da Rocha et al, 2012).…”
Section: Application Of the Uppsala Stage Theory Of Internationalisationmentioning
confidence: 99%
“…Similar with the broader entry mode research agenda, a key question in the analysed literature (14%, 10 studies) is whether EMMs follow the path dependent logic proposed by conventional applications of the Uppsala theory. Some concluded that, since pioneering is probably not an option for most of these firms, EMMs follow a gradual expansion process as they learn about foreign markets and benefit from being fast market followers versus late entrants (Da Rocha et al, 2012).…”
Section: Application Of the Uppsala Stage Theory Of Internationalisationmentioning
confidence: 99%
“…Scholars (Rocha et al 2012) suggest that researchers should focus on international commitments. According to Hardwick et al (2013: 5), "… few studies actually explain the role played by trust."…”
Section: Introductionmentioning
confidence: 99%
“…The interviews lasted for over one and half hours. The use of multiple methods including interviews and relevant documentation helped to reduce the chances of misinterpretation (da Rocha, Cotta de Mello, Pacheco, & de Abreu Farias, ; Eisenhardt, ). The documentation inspired interview questions and provided an avenue to cross‐check on information received.…”
Section: Methodsmentioning
confidence: 99%
“…The documentation inspired interview questions and provided an avenue to cross‐check on information received. In‐depth face‐to‐face interviews were found to be suitable, as they gave rise for the opportunities to probe interviewees to uncover underlying reasons for their actions (da Rocha et al, ).…”
Section: Methodsmentioning
confidence: 99%